Perencanaan PLTS Untuk SPKLU Tipe Fast Charging Dengan Objek Kendaraan Roda Dua - Dua Lembang, Aldino Purwanto; Haerani; Firman; Marhatang; Jamal (Jurnal Teknik Mesin Sinergi, 2026)
This study aims to develop a design for a Public Electric Vehicle Charging Station of the fast-charging type for two-wheeled vehicles powered by a Solar Power Plant. The system is designed to support the clean energy transition and provide a sustainable charging solution. The Electric Vehicle Charging Station is assembled using a single solar panel with a capacity of 375 WP, a 12V 100Ah storage battery, an MPPT 60A controller, a 1200W 20A boost step-up converter, a 24V DC fan, a diode, and a battery capacity module. The test results show that the lithium-ion battery with an initial voltage of 48V and an initial charging current of 2.57A reached full charge (52V) within 1 hour and 30 minutes, while the SLA battery with an initial voltage of 52V and an initial charging current of 0.56A reached 52.8V in 3 hours and 10 minutes. The system demonstrated component stability, particularly in the boost converter, and operated effectively with a constant input power of 81.33W. However, the 12V 100Ah storage battery capacity was insufficient to charge more than one battery, indicating the need for a larger storage capacity.